Egri csillagok - Várkonyi, Zoltán (Hungary : Mokép, 1968)
The story begins with an idyllic picture: two children are bathing in a brook, Gergő (Gergely), the orphan of a blacksmith and Vicuska (Éva), the daughter of a wealthy man. They are disturbed by a Turkish soldier, who takes them prisoner. As they travel with the other Turkish captives, they overhear two bandits planning to rob their village. They escape during the night, go home and with the help of a brave Hungarian soldier they organize the defense of the village. Dobó, the defender, takes Gergő with him to the court of the noble Bálint Török, who raises him together with his own sons. Eight years later young Gergely plans to blow up the sultan, but fails, and is taken prisoner. While in captivity, he gets hold of the secret map of the fortress of Eger. He manages to escape again and returns home to meet his childhood love, Éva, but discovers that her family has moved to the royal court of Buda. There he meets the young woman and they exchange vows of love. Meanwhile Bálint Török and the infant king receive the Turkish sultan, who cheats him, takes Buda by force and drags him off to captivity. Gergely determined to go to Constantinople and help him escape. Before setting off, he receives the news that Éva is to be forced to marry a captain, elopes with her from the wedding and marries her. Together with Török’s son, they travel to Constantinople dressed as Italian musicians where they meet the old prisoner. Almost ten years pass and the Turks set off to besiege Eger. The enemy is far superior in numbers and the king fails to send the promised relief force. A long and heavy siege follows, and even the women of Eger take part. After the hard-fought battle the Hungarians win, Éva and Gergely meet again.
Duration: 02:23:00
Keywords: Fiction films